2021
DOI: 10.1007/s00484-021-02095-z
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous anandamide and self-reported pain are significantly reduced after a 2-week multimodal treatment with and without radon therapy in patients with knee osteoarthritis: a pilot study

Abstract: Multimodal therapies comprising spa applications are widely used as non-pharmaceutical treatment options for musculoskeletal diseases. The purpose of this randomized, controlled, open pilot study was to elucidate the involvement of the endocannabinoid system in a multimodal therapy approach. Twenty-five elderly patients with knee osteoarthritis (OA) received a 2-week spa therapy with or without combination of low-dose radon therapy in the Bad Gastein radon gallery. A 10-point numerical rating scale (pain in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…In one of the most well-known radon spa galleries in Bad Gastein, Austria, patients receive approximately 44 kBq/m 3 radon/therapy session in the course of 10 treatment sessions, each lasting for the duration of one hour. Unlike in our experiment where we wanted to focus on only radon-induced effects, therapy includes enhanced temperature (37–41.5 °C) and humidity (70–100%) [ 1 , 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In one of the most well-known radon spa galleries in Bad Gastein, Austria, patients receive approximately 44 kBq/m 3 radon/therapy session in the course of 10 treatment sessions, each lasting for the duration of one hour. Unlike in our experiment where we wanted to focus on only radon-induced effects, therapy includes enhanced temperature (37–41.5 °C) and humidity (70–100%) [ 1 , 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Next to the discomfort of patients that fail conventional therapies, all of these diseases bear a relatively high socioeconomic burden. Here, a therapy utilizing radon might be a useful additional therapy option, especially with regard to pain management [1,[5][6][7][8], similar to observations made in the treatment of chronic, inflammatory diseases with low doses of X-rays [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thermal/spa treatments, specially water immersion, have shown to benefit cardiovascular and neuromuscular systems (4). Its use has shown to be beneficial for healthy older adults (5) as well as older people with different conditions, including Parkinson's disease (6), and constipation (7), but thermal/spa therapy are the most often used for the treatment of osteoarticular diseases in older adults (8)(9)(10)(11). A randomized controlled trial (10) showed spa therapy (including balneotherapy and jet shower), compared to etodolac treatment, improved pain, anxiety, and quality of life in older adults with generalized osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%